Половой диморфизм больших слюнных желез у грызунов; Морфология; Т. 149, вып. 2 - Иванова В. В. Вера Владимировна; Мильто И. В. Иван Васильевич; Суходоло И. В. Ирина Владимировна; Серебрякова О. Н. Ольга Николаевна; Бузенкова А. В. Ангелина Владиславовна (2016, 2016)
Заглавие с экрана